USING CLIL TECHNOLOGY IN TRAINING TO A FOREIGN LANGUAGE - Khalilova Olima Akhatovna (Western European Studies, 2024)
This article discusses the concept of Content and Language Integrated Learning (CLIL) and its role in the modern educational system. The implementation of this modern technology requires a systematic approach to teaching, as well as the willingness and desire of teachers to use this technique. The advantages and difficulties of this technology that a teacher may encounter in the process of teaching a foreign language are analyzed.
Keywords: CLIL method; teacher; foreign language; subject